Differential Drive Mobile Robot Motion Accuracy Improvement with Odometry-Compass Sensor Fusion Implementation - Sungkono Sungkono; Gillang Al Azhar; Adi Candra Kusuma; Syarifatul Izza (ELKHA : Jurnal Teknik Elektro, 2023)
The Implementation of wheeled robot technology in the development of transportation vehicles makes them capable for operating automatically. In order to operate automatically, a vehicle requires stable control system which including motion kinematic algorithm where is developed in a robotic system. With the aim of being able to build an Unmanned Grounded Vehicle (UGV), in this study an UGV prototype was made in the form of a wheeled robot with Differential Drive Mobile Robot (DDMR) system. The robot is controlled by motion kinematic control algorithm and a trajectory tracking system that is used to get an estimate of the position caused by the robot’s movement, beside it made the robot can operate automatically. To support the performance of the control system, the robot prototype is added with a compass sensor which used as the wheel odometry sensor’s support. The process of combining wheel odometry and compass sensor data is carried out by using the sensor fusion algorithm, where the limit value for the RMS error for the position accuracy is not more than 0.15 meters. As the result of the trials, by adding a compass sensor and implementing sensor fusion algorithm is able to reduce the average RMS (Root Mean Square) error value of the motion accuracy into below 0.15 meters which previously worth 0.392 meters decreased into 0.075 meters.